Schistosoma mansoni venom allergen like proteins present differential allergic responses in a murine model of airway inflammation. - Leonardo Paiva Farias; Dunia Rodrigues; Vinicius Cunna; Henrique Krambeck Rofatto; Eliana L Faquim-Mauro; Luciana C C Leite (Public Library of Science (PLoS), 2012)
BACKGROUND: The Schistosoma mansoni Venom-Allergen-Like proteins (SmVALs) are members of the SCP/TAPS (Sperm-coating protein/Tpx-1/Ag5/PR-1/Sc7) protein superfamily, which may be important in the host-pathogen interaction. Some of these molecules were suggested by us and others as potential immunomodulators and vaccine candidates, due to their functional classification, expression profile and predicted localization. From a vaccine perspective, one of the concerns is the potential allergic effect of these molecules. METHODOLOGY/PRINCIPAL FINDINGS: Herein, we characterized the putative secreted proteins SmVAL4 and SmVAL26 and explored the mouse model of airway inflammation to investigate their potential allergenic properties. The respective recombinant proteins were obtained in the Pichia pastoris system and the purified proteins used to produce specific antibodies. SmVAL4 protein was revealed to be present only in the cercarial stage, increasing from 0-6 h in the secretions of newly transformed schistosomulum. SmVAL26 was identified only in the egg stage, mainly in the hatched eggs' fluid and also in the secretions of cultured eggs. Concerning the investigation of the allergic properties of these proteins in the mouse model of airway inflammation, SmVAL4 induced a significant increase in total cells in the bronchoalveolar lavage fluid, mostly due to an increase in eosinophils and macrophages, which correlated with increases in IgG1, IgE and IL-5, characterizing a typical allergic airway inflammation response. High titers of anaphylactic IgG1 were revealed by the Passive Cutaneous Anaphylactic (PCA) hypersensitivity assay. Additionally, in a more conventional protocol of immunization for vaccine trials, rSmVAL4 still induced high levels of IgG1 and IgE. CONCLUSIONS: Our results suggest that members of the SmVAL family do present allergic properties; however, this varies significantly and therefore should be considered in the design of a schistosomiasis vaccine. Additionally, the murine model of airway inflammation proved to be useful in the investigation of allergic properties of potential vaccine candidates.